Peran Dosen Dalam Meningkatkan Motivasi Belajar Mahasiswa Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta (STITMA) - Muhammad Ibnu Wahyudin; Hilalludin Hilalludin; Adi Haironi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The role of lecturers in enhancing the quality of higher education is significant, particularly in increasing students' motivation to learn. This study aims to evaluate the role of lecturers in boosting students' learning motivation at STITMA Yogyakarta. A qualitative method was employed, with primary data obtained through observation and secondary data from literature studies. The findings indicate that academic advisors not only provide academic guidance but also act as intermediaries between students and the university, encouraging active participation in both academic and non-academic activities. Internal factors such as health, intelligence, and motivation, along with external factors like family support, teaching methods, and the social environment, significantly influence students' learning motivation. The implications of this study suggest that lecturers need to understand and leverage these factors to create a supportive learning environment that motivates students to achieve optimal academic performance.